Potensi Tandan Kosong Sawit sebagai Bahan Bakar Padat: Analisis Degradasi Termal - Maarasyid, Cici; Idayu, Ida; Zulfansyah; Israyandi; Legawati, Lisa; Ermal, Dini Aulia Sari; Rawadi, Raihan; Olivia, Cindy; Fitri, Suchy Arum; Aderiani, Suci (Fakultas Teknik UMRI, 2023)
The availability of oil palm empty fruit bunches in Indonesia could be an important source of biomass to be utilized as a solid fuel feedstock. In this work, the thermal behavior and degradation of oil palm emty fruit bunches was investigated with a thermogravimetric analyzer in nitrogen atmosphere. The samples were heated from room temperature to 900 oC at heating rates of 20 oC min-1. The ultimate and proximate analysis revealed that oil palm empty fruit bunches contains high volatile matter, fixed carbon and ash content while the caliric value was 17.87 MJ/kg. Thermogravic analysis results indicated thermal degradation of samples occurs in three stages, namely drying and evaporation, active degradation and passive degradation. In addition, active degradation commenced at 148 oC with a peak of degradation temperature of 322.5 oC resulting in 68.32% weight loss.